A MANAGEMENT PERSONNEL IS TAKING INTO ACCOUNT CORPORATE SOCIAL RESPONSIBILITY OF ENTERPRISES - CHEREP, OLEKSANDR; KONEVA, A. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Every year the issues of corporate social responsibility (corporate social responsibility) become more relevant for Ukraine, which is due to the following groups of reasons: first, companies are increasingly influenced by the external environment and must respond to its challenges, in particular on social guidelines. ; secondly, as labor is intellectualized, the role of human capital increases, employees’ understanding of the concept of a decent job, fair remuneration for work, employment efficiency gradually changes, and their requirements for the employer’s company increase; thirdly, the dissemination of the principles of openness and transparency of companies makes available to employees and consumers any information about the operation of the company, therefore, the importance of a good image is growing; fourth, the interest of potential investors in information about the company’s competitiveness, concern for the environment, social responsibility, etc. is increasing. Therefore, the issue of personnel management on the basis of forming a strategy of corporate social responsibility is timely and relevant. Modern of approaches are investigational and authorial determination of essence of concept of «management a personnel» of is given. Basic of directions of activity are exposed in a management a personnel. Main of aspects are certain in a management a personnel, description is given to them. Properties of management a personnel are marked on the basis of complex decision of problems and their recreation. It of is distinguished objects, subjects of and objects in the management of enterprises a personnel. Effective of methods are certain of management a personnel which gives an opportunity to promote job performances as separate workers so whole enterprise on the whole. Reasonably of intercommunication of between the processes of management a personnel and corporate social responsibility. Expediency of conduct of socially responsible business is well - proven, that conditioned: by the improvement of reputation of enterprise and brand; by the decline of risks and fluidity of shots; by the increase of the labour productivity; adjusting of partner relationships with the state, partners and employees. Priority of directions of corporate social responsibility, which are the mortgage of successful and harmonious development of society, decision social economic and ecological problems, are distinguished.